Resilience and personal effectiveness for social workers - Greer, Jim (Sage Publications Ltd, 2016)
Social work in the 21st century is facing great change and upheaval in a period of Government austerity measures. From worsening pay rates to limited resources, these are increasingly challenging times in which social workers practice. It is therefore important that social work students are prepared for the realities of working within the modern social care system - that they have the tools and skills to care for themselves, and not just others. This book is a straightforward guide on how to cope with the stress and pressures of today’s social work environment by developing the right skills and knowledge. It will help students learn from a very early stage how to be at their best; from developing strategies to look after themselves and making the best use of supervision to the support they need to dealing with bullies and/or difficult people - all essential guidance on how to improve their health and mental wellbeing and prepare them to manage the challenges they will face. Quelle=Source: Verlag/Publisher.